Expressway shallow layer grouting repair process

By adding nano-silica, phytol-hexaphosphate and surface-modified vitrified microbeads to the two-component grouting material, the mechanical properties of the TPU foam are significantly improved, and the problem of insufficient mechanical properties of the TPU foam in the prior art is solved. , achieving higher compression strength and bond strength, meeting the road performance standards for highway repair.

CN119145265APending Publication Date: 2024-12-17TIANJIN XINZHAN EXPRESSWAY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411257621.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In the existing two-component grouting materials, in the shallow grouting repair of highways, the cell structure of TPU foam is large and the particle surface is not smooth, resulting in insufficient mechanical and practical performance and cannot meet the current road performance standards.

Method used

Using additives such as nanosilica, phytol hexaphosphate and surface modified vitrified microbeads, nanosilica and phytol hexaphosphate are added to component A, and surface modified vitrification is used in component B. Microbeads significantly improve the mechanical stability and cross-linking degree of TPU foam, and improve the cell structure and mechanical properties.

Benefits of technology

It significantly improves the maximum compression strength of TPU foam, which is 45% higher than ordinary TPU foam, and has good bonding strength and maximum compression strength, reaching 3.55MPa and above.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005034559530000111
    Figure BDA0005034559530000111
  • Figure BDA0005034559530000121
    Figure BDA0005034559530000121
  • Figure HDA0005034559540000011
    Figure HDA0005034559540000011
Patent Text Reader

Abstract

The invention relates to the technical field of highway construction, and particularly discloses an expressway shallow layer grouting repair process which comprises the following steps: hole arrangement, hole drilling and hole cleaning, sealing ring pre-burying, grouting, hole sealing and pressure stabilizing, and pavement recovery, grouting adopts a double-component grouting material for double-liquid grouting, and the double-component grouting material comprises a component A and a component B, the component A comprises composite polyol, a catalyst, a foam stabilizer and a flexibilizer, the component B comprises isocyanate, the flexibilizer comprises nano-silica and inositol hexaphosphate according to a weight ratio of (2-3.5): 10, and the component B further comprises surface modified vitrified microbeads accounting for 30wt%-40wt% of the isocyanate. The pavement repaired by the shallow grouting repair process is subjected to sampling detection, the maximum compression strength of an obtained sample is not lower than 3.55 MPa, and the bonding strength is not lower than 1.05 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of highway construction, and in particular to a shallow grouting repair process for highways. Background Art

[0002] Semi-rigid base is a common structural type used in my country's high-grade highways. Under the influence of factors such as material shrinkage, temperature shrinkage, and vehicle load, a large number of cracks will occur, which not only destroys the integrity and strength of the pavement structure, but also seriously reduces the quality and service life of the road. It is a major problem that plagues the road maintenance industry. For the traditional treatment technology of cracks in semi-rigid base, the "disembowelment" excavation and repair method has great interference with traffic, high cost, and great limitations in use. Therefore, the shallow grouting repair technology of pavement cracks has great development advantages as a non-excavation repair technology.

[0003] The technical principle of shallow grouting to repair road cracks is to inject two-component grouting materials into the pavement base through a smaller borehole in a certain proportion. When the two-component grouting materials meet, a polymerization reaction occurs, releasing a large amount of heat and gas, causing the volume of the grouting material to expand rapidly, and continuously penetrate and diffuse around along the cracks in the structural layer, eventually forming a foam-like solid with a certain strength and stability, which can effectively fill and seal the cracks inside the structural layer, and recombine the loose particles inside the structural layer, thereby restoring the integrity of the pavement structure, improving the bearing capacity of the pavement structure, and achieving the purpose of minimally invasive repair of pavement structure cracks.

[0004] As the shallow grouting repair process has received more and more attention in related fields, its repair effect is bound to face higher requirements. The most commonly used two-component grouting materials at present include polyols and isocyanates. When mixed under catalytic conditions, the two will generate polyurethane (TPU) foam with high elasticity and high waterproof ability. However, the pore structure size of TPU foam is large, and the surface of the particles is not smooth, which will affect its mechanical properties and performance. The defect reflected in the grouting repair is its low compression strength, which leads to the service life of the road after TPU foam repair cannot meet the current road performance standards. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a shallow grouting repair process for highways.

[0006] The present application provides a shallow grouting repair process for a highway, comprising the following steps: hole arrangement, hole drilling and hole cleaning, pre-embedded sealing rings, grouting, hole sealing and pressure stabilization, and road surface restoration. The grouting adopts a two-component grouting material for two-liquid grouting. The two-component grouting material comprises a component A and a component B. The component A comprises a composite polyol, a catalyst, a uniform foaming agent and a toughening agent. The component B comprises isocyanate. The toughening agent comprises nano-silicon dioxide and phytic acid in a weight ratio of (2-3.5):10. The component B also comprises surface-modified glass microspheres in an amount of 30wt%-40wt% of the amount of isocyanate.

[0007] By adopting the above technical scheme, the present application adds nano-silicon dioxide and phytic acid to component A, wherein nano-silicon dioxide can significantly improve the mechanical stability of TPU foam pores. Phytic acid contains a large number of phosphate groups. When component A is mixed with component B, a large amount of heat will be generated. These phosphate groups will react with the hydroxyl groups on the polyol when heated and form a dense network structure, thereby improving the degree of cross-linking inside the TPU foam, making it more dense and stable. The present application also adds surface-modified glass microspheres to component B and closely combines with other raw materials in the system. It has good compressive strength, fluidity and stability, can be fully dispersed in the system and form stable chemical bonds with the polyurethane matrix, and improves the pore structure and mechanical properties of the TPU foam.

[0008] Therefore, this application fully utilizes the synergistic effect of the three by adding nano-silica, phytic acid and surface-modified glass microspheres, significantly improving the mechanical strength of TPU foam. Compared with ordinary TPU foam, the maximum compressive strength is increased by 45%, and the minimum can reach 3.55MPa.

[0009] The present application strictly controls the weight ratio of nano-silica and phytic acid. If the amount of nano-silica is too large, the viscosity in component A will increase, and the nano-silica will be unevenly dispersed, resulting in reduced mechanical properties of the TPU foam obtained in the end; if the amount of phytic acid is too large, the hydroxyl sites on the polyol will be excessively occupied, resulting in a decrease in the degree of crosslinking between isocyanate and polyol, which will lead to uneven pores in the TPU foam. The present application also strictly controls the amount of surface-modified glass microspheres added, so that the optimization degree of the pore structure and mechanical properties of the TPU foam is greater. If the amount added is too small, the expected reinforcement effect cannot be achieved. If the amount added is too large, the surface-modified glass microspheres will agglomerate in the system, the dispersibility will be reduced, the pore size will increase, and the number of open and broken bubbles will increase, which will reduce the mechanical strength of the TPU foam.

[0010] Preferably, the surface modified vitrified microspheres are prepared by the following method: The glass microspheres are subjected to flotation treatment, hydroxylation treatment, and amino modification treatment to obtain the glass microspheres to be modified. Subsequently, the glass microspheres to be modified and MDI in a weight ratio of 2:(0.5-0.6) are dispersed in an organic solvent, and the reaction is stirred at a temperature of 78-82°C for 2-2.2h. After that, the solid matter is taken out, washed with an organic solvent, filtered under reduced pressure, and vacuum dried until the system reaches a constant weight to obtain surface-modified glass microspheres.

[0011] By adopting the above technical scheme, the present application mixes the glass microspheres to be modified after flotation treatment, hydroxylation treatment and amino modification treatment with MDI and reacts them under certain conditions to obtain surface-modified glass microspheres. The NCO groups carried by MDI are grafted on the surface of the glass microspheres, so that the surface-modified glass microspheres can react with the polyether polyol in component A to form stable chemical bonds when component A and component B are mixed. Compared with directly adding glass microspheres or glass microspheres to be modified, the surface-modified glass microspheres can further improve the cross-linking density in the system, thereby significantly improving the mechanical strength of the TPU foam.

[0012] Preferably, the weight ratio of nano-silicon dioxide to phytic acid is 3:10.

[0013] By adopting the above technical solution, the present application controls the weight ratio of nano-silicon dioxide and phytic acid to 3:10, and experimental data show that the compression strength of the TPU foam can reach 3.71 MPa at this time.

[0014] Preferably, the amount of the surface modified glass microspheres is 35 wt % of the amount of isocyanate.

[0015] By adopting the above technical solution, the application controls the amount of surface-modified glass microspheres to 35wt% of the amount of isocyanate, and experimental data show that the compression strength of the TPU foam can reach 3.78MPa.

[0016] Preferably, the nano-silica is nano-silica modified by a silane coupling agent.

[0017] Preferably, the complex polyol comprises polyol A with a molecular weight of 500 and polyol B with a molecular weight of 5000, and the weight ratio of polyol A to polyol B is 80:(15-25).

[0018] Preferably, the weight ratio of polyol A to polyol B is 80:20.

[0019] By adopting the above technical scheme, the present application uses polyol A and polyol B of different molecular weights in a certain proportion, wherein polyol A can provide TPU foam with a hard segment polyurethane with good mechanical strength, and polyol B can provide TPU foam with a soft segment polyurethane with high bonding ability. The present application also strictly controls the weight ratio of polyol A to polyol B, so that the bonding strength and maximum compression strength of the TPU foam tend to be balanced, and because the addition of nano-silica, inositol hexaphosphate and surface-modified glass microspheres in the present application significantly optimizes the mechanical properties of the TPU foam, the proportion of polyol B in the present application is greater than that of ordinary two-component grouting materials, so the TPU foam of the present application has both good bonding strength and maximum compression strength. Experimental data proves that when the weight ratio of polyol A to polyol B is 80:20, the bonding strength and maximum compression strength of the TPU foam can achieve an optimal balance.

[0020] Preferably, the foam leveling agent in the A component is prepared by the following method: low hydrogen silicone oil and allyl polyether are placed in a negative pressure environment for dehydration respectively, and then mixed under the protection of an inert gas so that the molar ratio of Si-H to C=C in the system is 1:(3-4), chloroplatinic acid is added, and then the temperature is raised to 105-110°C for reaction for 2-2.5h to obtain a foam leveling agent.

[0021] Preferably, the amount of chloroplatinic acid added is 0.01-0.015wt‰ of the total amount of the low hydrogen silicone oil and the allyl polyether.

[0022] By adopting the above technical scheme, the present application uses a certain molar ratio of low-hydrogen silicone oil and allyl polyether to mix, and under the catalytic effect of a certain amount of chloroplatinic acid and a certain temperature, a leveling agent that acts in the TPU foam formation process is prepared. The leveling agent has a low viscosity and can be fully mixed with other components in the system. The TPU foam has finer pores and a more uniform pore structure during foaming, and the compression strength of the TPU foam is also higher.

[0023] In summary, this application has the following beneficial technical effects: 1. In the shallow grouting repair process of the highway in the present application, nano-silica, inositol hexaphosphate and surface-modified vitrified microspheres are added to the two-component grouting material, and the three give full play to the synergistic effect, significantly improving the mechanical strength of the TPU foam. Compared with the maximum compression strength of ordinary TPU foam, it is increased by 45% and can reach 3.55MPa; 2. In the shallow grouting repair process of the highway of the present application, the proportion of polyol B in the two-component grouting material is greater than that in the ordinary two-component grouting material. Therefore, the TPU foam of the present application has both good bonding strength and maximum compression strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1The radar detection images of cracks before and after grouting; Figure 2 Schematic diagram of sampling.

[0025] Material Source Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically: Vitrified microspheres were purchased from Lingshou County Maozhuo Building Materials Co., Ltd., with a particle size of 120 mesh; Silane coupling agent was purchased from Dongguan Kangjin New Material Technology Co., Ltd., model KH550; MDI was purchased from Shanghai Aladdin Reagent Co., Ltd., analytical grade; DMF was purchased from Tianjin Tianli Chemical Reagent Co., Ltd., analytical grade; Nano-silicon dioxide was purchased from Ningbo Jinlei Nanomaterial Technology Co., Ltd., with a specific surface area of ​​380 m 2 / kg; N-Methylpyrrolidone was purchased from Jinan Zekuan Chemical Co., Ltd., CAS No. 872-50-4; Low hydrogen silicone oil was purchased from Jinan Junteng Chemical Co., Ltd., CAS No. 63148-57-2; Allyl polyether was purchased from Haian Petrochemical Plant, Jiangsu Province. n =1500; Chloroplatinic acid was purchased from Shanghai Ciyu Chemical Technology Co., Ltd.; Polyol A was purchased from Hubei Langbowan Biopharmaceutical Co., Ltd. with a molecular weight of 500; Polyol B was purchased from Sangda Chemical Co., Ltd. with a molecular weight of 5000; Triethylenediamine was purchased from Jining Huakai Resin Co., Ltd., industrial grade; Phytic acid was purchased from Shanghai MacLean Biochemical Co., Ltd. with a purity of 70 wt%; Isocyanate was purchased from Jining Huakai Resin Co., Ltd., CAS No. 9016-87-9; The present application is further described in detail below with reference to examples and comparative examples.

[0026] Preparation Example 1.1 The preparation method of surface modified vitrified microspheres comprises the following steps: I. Flotation treatment: 60 kg of vitrified microspheres were placed in water, stirred thoroughly, and allowed to stand for 3 hours before being poured out. The floating beads on the upper layer were washed with distilled water for 3 times, and then filtered and dried. II. Hydroxylation treatment: Add the flotation-treated and dried glass microspheres into a 0.3 mol / L sodium hydroxide solution, reflux and stir in an oil bath at 80°C for 2 h for hydroxylation treatment, with a stirring reaction speed of 50 r / min, then filter under reduced pressure and wash the glass microspheres with distilled water until the pH is neutral, and vacuum dry at 100°C for 10 h; III. Amino modification treatment: The glass microspheres after hydroxylation treatment and drying were dispersed in 100 kg of anhydrous ethanol aqueous solution with an anhydrous ethanol concentration of 75 wt%, and then 33 kg of silane coupling agent was added to the solution, refluxed and stirred at 80 ° C for 3 h, repeatedly washed with anhydrous ethanol aqueous solution, filtered under reduced pressure, and vacuum dried at 100 ° C for 10 h to obtain the glass microspheres to be modified; IV. Modification treatment: 50 kg of the glass microspheres to be modified and 12.5 kg of MDI were fully dispersed in DMF, stirred and reacted at 78 ° C for 2.2 h, and finally washed repeatedly with DMF, filtered under reduced pressure, and vacuum dried at 100 ° C for 10 h until the system reached constant weight to obtain surface-modified glass microspheres.

[0027] Preparation Example 1.2 The preparation method of surface modified vitrified microspheres comprises the following steps: I. Flotation treatment: 60 kg of vitrified microspheres were placed in water, stirred thoroughly, and allowed to stand for 3 hours before being poured out. The floating beads on the upper layer were washed with distilled water for 3 times, and then filtered and dried. II. Hydroxylation treatment: Add the flotation-treated and dried glass microspheres into a 0.3 mol / L sodium hydroxide solution, reflux and stir in an oil bath at 80°C for 2 h for hydroxylation treatment, with a stirring reaction speed of 50 r / min, then filter under reduced pressure and wash the glass microspheres with distilled water until the pH is neutral, and vacuum dry at 100°C for 10 h; III. Amino modification treatment: The glass microspheres after hydroxylation treatment and drying were dispersed in 100 kg of anhydrous ethanol aqueous solution with an anhydrous ethanol concentration of 75 wt%, and then 33 kg of silane coupling agent was added to the solution, refluxed and stirred at 80 ° C for 3 h, repeatedly washed with anhydrous ethanol aqueous solution, filtered under reduced pressure, and vacuum dried at 100 ° C for 10 h to obtain the glass microspheres to be modified; IV. Modification treatment: 50 kg of the glass microspheres to be modified and 13.75 kg of MDI were fully dispersed in DMF, stirred and reacted at 80 ° C for 2.1 h, and finally repeatedly washed with DMF, filtered under reduced pressure, and vacuum dried at 100 ° C for 10 h until the system reached constant weight to obtain surface-modified glass microspheres.

[0028] Preparation Example 1.3 The preparation method of surface modified vitrified microspheres comprises the following steps: I. Flotation treatment: 60 kg of vitrified microspheres were placed in water, stirred thoroughly, and allowed to stand for 3 hours before being poured out. The floating beads on the upper layer were washed with distilled water for 3 times, and then filtered and dried. II. Hydroxylation treatment: Add the flotation-treated and dried glass microspheres into a 0.3 mol / L sodium hydroxide solution, reflux and stir in an oil bath at 80°C for 2 h for hydroxylation treatment, with a stirring reaction speed of 50 r / min, then filter under reduced pressure and wash the glass microspheres with distilled water until the pH is neutral, and vacuum dry at 100°C for 10 h; III. Amino modification treatment: The glass microspheres after hydroxylation treatment and drying are dispersed in 100 kg of anhydrous ethanol aqueous solution with an anhydrous ethanol concentration of 75 wt%, and then 33 kg of silane coupling agent is added to the solution, refluxed and stirred at 80 ° C for 3 hours, repeatedly washed with anhydrous ethanol aqueous solution, filtered under reduced pressure, and vacuum dried at 100 ° C for 10 hours to obtain the glass microspheres to be modified; IV. Modification treatment: 50 kg of the glass microspheres to be modified and 15 kg of MDI are fully dispersed in DMF, stirred and reacted at 82 ° C for 2 hours, and finally repeatedly washed with DMF, filtered under reduced pressure, and vacuum dried at 100 ° C for 10 hours until the system is constant weight to obtain surface modified glass microspheres.

[0029] Preparation Example 2 The preparation method of silane coupling agent modified nano silicon dioxide comprises the following steps: 20 kg of nano-silica was dried at 200 °C under vacuum conditions for 4 hours, diluted with a certain amount of N-methylpyrrolidone and then ultrasonically dispersed for 30 minutes to form a suspension, 14 kg of silane coupling agent was diluted with N-methylpyrrolidone and added to the suspension, reacted in a 90 °C oil bath for 4 hours, centrifuged after cooling, and repeatedly washed with ethanol. After centrifugation, it was dried in an oven at 60 °C for 24 hours to obtain silane coupling agent modified nano-silica.

[0030] Preparation Example 3.1 The preparation method of the foam leveling agent comprises the following steps: The low-hydrogen silicone oil and allyl polyether were placed in a negative pressure environment at a temperature of 120°C for dehydration, and then mixed under the protection of an inert gas so that the molar ratio of Si-H to C=C in the system was 1:3. The temperature was adjusted to 80°C, and 0.01wt‰ of chloroplatinic acid was added to the total amount of the low-hydrogen silicone oil and allyl polyether. The temperature was then raised to 110°C for reaction for 2h to obtain a uniform foaming agent.

[0031] Preparation Example 3.2 The preparation method of the foam leveling agent comprises the following steps: The low hydrogen silicone oil and allyl polyether were placed in a negative pressure environment at a temperature of 120°C for dehydration, and then mixed under the protection of an inert gas so that the molar ratio of Si-H to C=C in the system was 1:4. The temperature was adjusted to 80°C, and 0.015wt‰ of chloroplatinic acid was added to the total amount of the low hydrogen silicone oil and allyl polyether. The temperature was then raised to 105°C for reaction for 2.5h to obtain a uniform foaming agent.

[0032] Preparation Example 3.3 The preparation method of the foam leveling agent comprises the following steps: The low hydrogen silicone oil and allyl polyether were placed in a negative pressure environment at a temperature of 120°C for dehydration, and then mixed under the protection of inert gas to make the molar ratio of Si-H to C=C in the system be 1:3.5. The temperature was adjusted to 80°C, and 0.012wt‰ of chloroplatinic acid was added to the total amount of the low hydrogen silicone oil and allyl polyether. The temperature was then raised to 105°C for reaction for 2.5h to obtain a uniform foaming agent.

[0033] Preparation Example 3.4 The preparation method of the foam leveling agent is different from that of Preparation Example 3.1 in that the molar ratio of Si-H to C=C in the system is 1:2, and the rest is the same as that of Preparation Example 3.1.

[0034] Preparation Example 3.5 The preparation method of the foam leveling agent is different from that of Preparation Example 3.1 in that the molar ratio of Si-H to C=C in the system is 1:5, and the rest is the same as that of Preparation Example 3.1.

[0035] Preparation Example 3.6 The preparation method of the foam leveling agent is different from that of Preparation Example 3.1 in that the amount of chloroplatinic acid added is 0.008wt‰ of the total amount of the low-hydrogen silicone oil and the allyl polyether, and the rest is the same as Preparation Example 3.1.

[0036] Preparation Example 3.7 The preparation method of the foam leveling agent is different from that of Preparation Example 3.1 in that the amount of chloroplatinic acid added is 0.018wt‰ of the total amount of the low-hydrogen silicone oil and the allyl polyether, and the rest is the same as that of Preparation Example 3.1.

[0037] Preparation Example 3.8 The preparation method of the foam leveling agent is different from that of Preparation Example 3.1 in that the temperature is raised to 100°C after adding chloroplatinic acid, and the rest is the same as Preparation Example 3.1.

[0038] Preparation Example 3.9 The preparation method of the foam leveling agent is different from that of Preparation Example 3.1 in that the temperature is raised to 120°C after adding chloroplatinic acid, and the rest is the same as Preparation Example 3.1.

[0039] Example 1 A highway shallow grouting repair process comprises the following steps: A) Hole layout: according to the location of the cracks, use spray paint or a marker pen with a color that is significantly different from the road surface to mark the hole locations. The center spacing between adjacent holes is 35cm±5cm. The actual hole spacing should be determined based on the test section results. B) Drilling and hole cleaning: The drilling depth should be controlled according to the principle of "alternating deep and shallow". The depth of shallow holes should reach the bottom of the lower layer and exceed at least 5cm. The depth of deep holes should reach the space between the upper and lower base layers and exceed at least 5cm. The drill bit diameter is 20mm, and the drilling angle is vertical. During the drilling process, the dust in the hole and on the surface should be sucked away in time. After the drilling is completed, the dust in the hole should be cleaned to ensure that the hole is clean and dust-free; C) Pre-buried sealing ring: Shallow hole sealing kits should be buried in the middle surface layer of the original asphalt pavement, and deep hole sealing kits should be buried in the top surface of the upper base. The sealing kits should be buried to the specified depth as required, and should have a good sealing effect with the hole wall when driven into the hole, and should not be damaged; D1) Ingredients: 100 kg of composite polyol (84.2 kg of polyol A and 15.8 kg of polyol B), 3 kg of catalyst (triethylenediamine), 3 kg of the foam leveler prepared in Preparation Example 3.1 and 9 kg of toughening agent (1.5 kg of silane coupling agent modified nano-silica prepared in Preparation Example 2 and 7.5 kg of inositol hexaphosphate) were stirred in an electric stirrer for 20 min to obtain component A, and 100 kg of isocyanate and 30 kg of surface-modified glass microspheres prepared in Preparation Example 1.1 were ultrasonically dispersed at 40° C. for 30 min to obtain component B; D2) Grouting: Inject component A and component B into the grouting equipment, the grouting pump pressure is 0.5MPa, the grouting machine discharge pressure is 10MPa, the grouting needle is inserted and passes through the sealing kit, then open the valve to start grouting; E) Grouting termination: Grouting is terminated when one of the following phenomena occurs: ① The sealing kit pops up; ② The grouting pressure exceeds the set pressure; ③ Grout overflow occurs in adjacent holes, cracks, or grouting holes; ④ The cracks widen and new microcracks appear; ⑤ During the grouting operation, place a ruler on one side of the grouting hole, and when the feeler gauge gap changes by ≥2mm; F) Sealing and stabilizing pressure: After grouting stops, the grouting valve should be closed immediately, and the cork should be used to seal the hole for 5 minutes before being pulled out; G) Road surface restoration: Mill the old road to a depth of 5 cm, clean the bottom of the trench without leaving any interlayer, lay anti-cracking tape on the cracks at the bottom of the trench, lay 48 cm wide anti-cracking tape on the longitudinal cracks at the bottom of the trench, and lay 32 cm wide anti-cracking tape on the transverse cracks. Finally, lay a 5 cm modified asphalt concrete AC-13C top layer, lay the vertical tape at the vertical joints of the surface layer, spray tack oil between the asphalt surface layers, and the top layer of asphalt uses SBS ID type modified asphalt, and the top layer stone is basalt.

[0040] Example 2 A highway shallow grouting repair process comprises the following steps: A) Hole layout: according to the location of the cracks, use spray paint or a marker pen with a color that is significantly different from the road surface to mark the hole locations. The center spacing between adjacent holes is 38cm±5cm. The actual hole spacing should be determined based on the test section results. B) Drilling and hole cleaning: The drilling depth should be controlled according to the principle of "alternating deep and shallow". The depth of shallow holes should reach the bottom of the lower layer and exceed at least 5cm. The depth of deep holes should reach the space between the upper and lower base layers and exceed at least 5cm. The drill bit diameter is 20mm, and the drilling angle is vertical. During the drilling process, the dust in the hole and on the surface should be sucked away in time. After the drilling is completed, the dust in the hole should be cleaned to ensure that the hole is clean and dust-free; C) Pre-buried sealing ring: Shallow hole sealing kits should be buried in the middle surface layer of the original asphalt pavement, and deep hole sealing kits should be buried in the top surface of the upper base. The sealing kits should be buried to the specified depth as required, and should have a good sealing effect with the hole wall when driven into the hole, and should not be damaged; D1) Ingredients: 100 kg of composite polyol (76.2 kg of polyol A and 23.8 kg of polyol B), 3 kg of catalyst (triethylenediamine), 3 kg of the foam leveler prepared in Preparation Example 3.2 and 9 kg of toughening agent (2.0 kg of silane coupling agent modified nano-silica prepared in Preparation Example 2 and 7.0 kg of inositol hexaphosphate) were stirred in an electric stirrer for 20 min to obtain component A, and 100 kg of isocyanate and 33 kg of surface-modified glass microspheres prepared in Preparation Example 1.2 were ultrasonically dispersed at 40° C. for 30 min to obtain component B; D2) Grouting: Inject component A and component B into the grouting equipment, the grouting pump pressure is 0.3MPa, the grouting machine discharge pressure is 5MPa, the grouting needle is inserted and passes through the sealing kit, then open the valve to start grouting; E) Grouting termination: Grouting is terminated when one of the following phenomena occurs: ① The sealing kit pops up; ② The grouting pressure exceeds the set pressure; ③ Grout overflow occurs in adjacent holes, cracks, or grouting holes; ④ The cracks widen and new microcracks appear; ⑤ During the grouting operation, place a ruler on one side of the grouting hole, and when the feeler gauge gap changes by ≥2mm; F) Sealing and stabilizing pressure: After grouting stops, the grouting valve should be closed immediately, and the cork should be used to seal the hole for 3 minutes before being pulled out; G) Road surface restoration: Mill the old road to a depth of 5 cm, clean the bottom of the trench without leaving any interlayer, lay anti-cracking tape on the cracks at the bottom of the trench, lay 48 cm wide anti-cracking tape on the longitudinal cracks at the bottom of the trench, and lay 32 cm wide anti-cracking tape on the transverse cracks. Finally, lay a 5 cm modified asphalt concrete AC-13C top layer, lay the vertical tape at the vertical joints of the surface layer, spray tack oil between the asphalt surface layers, and the top layer of asphalt uses SBS ID type modified asphalt, and the top layer stone is basalt.

[0041] Example 3 A highway shallow grouting repair process comprises the following steps: A) Hole layout: according to the location of the cracks, use spray paint or a marker pen with a color that is significantly different from the road surface to mark the hole locations. The center spacing between adjacent holes is 33cm±5cm. The actual hole spacing should be determined based on the test section results. B) Drilling and hole cleaning: The drilling depth should be controlled according to the principle of "alternating deep and shallow". The depth of shallow holes should reach the bottom of the lower layer and exceed at least 5cm. The depth of deep holes should reach the space between the upper and lower base layers and exceed at least 5cm. The drill bit diameter is 20mm, and the drilling angle is vertical. During the drilling process, the dust in the hole and on the surface should be sucked away in time. After the drilling is completed, the dust in the hole should be cleaned to ensure that the hole is clean and dust-free; C) Pre-buried sealing ring: Shallow hole sealing kits should be buried in the middle surface layer of the original asphalt pavement, and deep hole sealing kits should be buried in the top surface of the upper base. The sealing kits should be buried to the specified depth as required, and should have a good sealing effect with the hole wall when driven into the hole, and should not be damaged; D1) Ingredients: 100 kg of composite polyol (79 kg of polyol A and 21 kg of polyol B), 3 kg of catalyst (triethylenediamine), 3 kg of the foaming agent prepared in Preparation Example 3.3 and 9 kg of toughening agent (2.3 kg of silane coupling agent modified nano-silica prepared in Preparation Example 2 and 6.7 kg of inositol hexaphosphate) were stirred in an electric stirrer for 20 min to obtain component A, and then 100 kg of isocyanate and 40 kg of surface-modified glass microspheres prepared in Preparation Example 1.3 were ultrasonically dispersed at 40° C. for 30 min to obtain component B; D2) Grouting: Components A and B were injected into the grouting equipment, the grouting feed pump pressure was 0.4 MPa, the grouting machine discharge pressure was 8 MPa, the grouting needle was inserted and passed through the sealing kit, and the valve was opened to start grouting; E) Grouting termination: Grouting is terminated when one of the following phenomena occurs: ① The sealing kit pops up; ② The grouting pressure exceeds the set pressure; ③ Grout overflow occurs in adjacent holes, cracks, or grouting holes; ④ The cracks widen and new microcracks appear; ⑤ During the grouting operation, place a ruler on one side of the grouting hole, and when the feeler gauge gap changes by ≥2mm; F) Sealing and stabilizing pressure: After grouting stops, the grouting valve should be closed immediately, and the cork should be used to seal the hole for 4 minutes before being pulled out; G) Road surface restoration: Mill the old road to a depth of 5 cm, clean the bottom of the trench without leaving any interlayer, lay anti-cracking tape on the cracks at the bottom of the trench, lay 48 cm wide anti-cracking tape on the longitudinal cracks at the bottom of the trench, and lay 32 cm wide anti-cracking tape on the transverse cracks. Finally, lay a 5 cm modified asphalt concrete AC-13C top layer, lay the vertical tape at the vertical joints of the surface layer, spray tack oil between the asphalt surface layers, and the top layer of asphalt uses SBS ID type modified asphalt, and the top layer stone is basalt.

[0042] Example 4 A shallow grouting repair process for a highway, which is different from Example 1 in that: in step D1, the amount of silane coupling agent modified nano-silica prepared in Preparation Example 2 is 2.08 kg, the amount of inositol hexaphosphate is 6.92 kg, and the rest is the same as Example 1.

[0043] Example 5.1 A shallow grouting repair process for a highway, which is different from Example 1 in that: in step D1, the amount of surface-modified vitrified microspheres prepared in Preparation Example 1.1 is 35 kg, and the rest is the same as Example 1.

[0044] Example 5.2 A shallow grouting repair process for a highway, which is different from Example 1 in that: in step D1, the amount of surface-modified vitrified microspheres prepared in Preparation Example 1.1 is 38 kg, and the rest is the same as Example 1.

[0045] Example 6.1 A shallow grouting repair process for a highway, which is different from Example 1 in that: in step D1, the amount of polyol A used is 80 kg, the amount of polyol B used is 20 kg, and the rest is the same as Example 1.

[0046] Example 6.2 A shallow grouting repair process for a highway, which is different from Example 1 in that: in step D1, the amount of polyol A used is 90 kg, the amount of polyol B used is 10 kg, and the rest is the same as Example 1.

[0047] Example 6.3 A shallow grouting repair process for a highway, which is different from Example 1 in that: in step D1, the amount of polyol A used is 70 kg, the amount of polyol B used is 30 kg, and the rest is the same as Example 1.

[0048] Examples 7.1-7.6 A shallow grouting repair process for a highway, which is different from Example 1 in that: in step D1, the uniform foaming agent prepared in Preparation Example 3.1 is replaced by the uniform foaming agents prepared in Preparation Examples 3.4-3.9 respectively, and the rest is the same as Example 1.

[0049] Comparative Example 1.1 The difference from Example 1 is that in step D1, the surface-modified glass microspheres prepared in Preparation Example 1.1 are removed, and the rest are the same as Example 1.

[0050] Comparative Example 1.2 The difference from Example 1 is that in step D1, the amount of surface-modified glass microspheres prepared in Preparation Example 1.1 is 50 kg, and the rest is the same as Example 1.

[0051] Comparative Example 2.1 The difference from Example 1 is that in step D1, the silane coupling agent-modified nano-silica prepared in Preparation Example 2 is removed, the amount of phytic acid used is 9 kg, and the rest is the same as Example 1.

[0052] Comparative Example 2.2 The difference from Example 1 is that in step D1, phytic acid is removed, the amount of silane coupling agent-modified nano-silica prepared in Preparation Example 2 is 9 kg, and the rest is the same as Example 1.

[0053] Comparative Example 3.1 The difference from Example 1 is that in step D1, the surface-modified glass microspheres prepared in Preparation Example 1.1, the silane coupling agent-modified nano-silica and phytic acid prepared in Preparation Example 2 are removed, and the rest are the same as Example 1.

[0054] Comparative Example 3.2 The difference from Example 1 is that in step D1, polyol B is removed, the amount of polyol A is 100 kg, the surface-modified glass microspheres prepared in Preparation Example 1.1, the silane coupling agent-modified nano-silica and phytic acid prepared in Preparation Example 2 are removed, and the rest are the same as Example 1.

[0055] Performance Testing 1. Radar monitoring: radar is used to detect the cracks before and after grouting, where a is a through crack, b is a poor interlayer, c is a loose base, and the red arrow is the grouting position. Figure 1 As shown; 2. Sampling and testing: Figure 2 As shown in the figure, the repaired pavement was sampled according to the records in T0903-2019 core drilling and cutting sampling method, and then the bonding strength and maximum compressive strength of the samples were measured according to GB / T 16777-2008 test method for building waterproof coatings and GB / T 8813-2020 determination of compression properties of rigid foam plastics, and the results are recorded in Table 1.

[0056] Table 1 Bond strength and maximum compressive strength records Data Analysis: As can be seen from Table 1, the bonding strength of Examples 1-3 of the present application can reach 1.05-1.08 MPa, and the maximum compressive strength can reach 3.55-3.62 MPa, which proves that the present application fully exerts the synergistic effect of the three by adding nano-silica, phytic acid and surface-modified glass microspheres, and significantly improves the mechanical strength of TPU foam, and the maximum compressive strength is increased by 45% compared with ordinary TPU foam; The maximum compressive strength of Example 4 is significantly greater than that of Example 1, which proves that the present application further optimizes the mechanical properties of TPU foam by strictly controlling the weight ratio of nano-silicon dioxide and phytic acid; The difference between Examples 5.1-5.2 and Example 1 is that the amount of surface-modified glass microspheres added is changed. The maximum compressive strength of Example 5.1 is significantly greater than that of Example 1 and Example 5.2, which proves that the present application optimizes the pore structure and mechanical properties of TPU foam to a greater extent by strictly controlling the amount of surface-modified glass microspheres added. In Examples 6.1-6.3, the present application changes the weight ratio of polyol A to polyol B, wherein the bonding strength and maximum compressive strength of Example 6.1 are both relatively high, while the bonding strength of Example 6.2 is extremely low, and the maximum compressive strength of Example 6.3 is also much lower than that of Example 1, proving that the present application achieves an optimal balance between the bonding strength and maximum compressive strength of the TPU foam obtained by strictly controlling the weight ratio of polyol A to polyol B; The maximum compressive strengths of Examples 7.1-7.6 are all lower than those of Example 1, which proves that the present application has obtained a foam leveler that can significantly homogenize the pores and has good fluidity by controlling the process parameters and raw material ratio in the foam leveler, so that the maximum compressive strength of the TPU foam has been significantly improved; The maximum compressive strength of Comparative Examples 1.1-1.2 is lower than that of Example 1, which proves that the present application optimizes the pore structure and mechanical properties of TPU foam to a greater extent by strictly controlling the amount of surface-modified glass microspheres added. If the amount added is too little, the expected reinforcement effect cannot be achieved. If the amount added is too large, the surface-modified glass microspheres will agglomerate in the system, the dispersibility will decrease, the pore size will increase, and the number of open and broken bubbles will increase, which will reduce the mechanical strength of TPU foam. The maximum compressive strength of Comparative Examples 2.1-2.2 is lower than that of Example 1, which proves that the present application gives full play to the synergistic effect of nano-silica and phytic acid, and further optimizes the mechanical properties of TPU foam. If the amount of nano-silica is too large, the viscosity in component A will increase, and the nano-silica will be unevenly dispersed, resulting in reduced mechanical properties of the final TPU foam; if the amount of phytic acid is too large, the hydroxyl sites on the polyol will be excessively occupied, resulting in a decrease in the crosslinking degree between isocyanate and polyol, which in turn leads to uneven pores of the TPU foam. The maximum compressive strength of comparative example 3.1 is only 2.50 MPa, which is much lower than that of example 1.1. This proves that the present invention, by adding nano-silica, phytic acid and surface-modified glass microspheres, gives full play to the synergistic effect of the three, and significantly improves the mechanical strength of TPU foam. Compared with ordinary TPU foam, the maximum compressive strength is increased by 1.12 MPa. The change between Comparative Example 3.2 and Example 1 is that the present application removes polyol B, increases the amount of polyol A that can provide TPU foam with hard segment polyurethane with good mechanical strength to 100 kg, removes polyol B with low mechanical strength, and removes nano-silica, phytic acid and surface-modified glass microspheres. However, the results show that even if the present application increases the amount of polyol A to the highest, the mechanical strength of the TPU foam obtained still cannot reach the mechanical strength of the TPU foam after adding nano-silica, phytic acid and surface-modified glass microspheres in the present application, and also loses the bonding strength, which proves that the polyol ratio of the present application and the addition of nano-silica, phytic acid and surface-modified glass microspheres can make the TPU foam have both good bonding strength and maximum compression strength.

[0057] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A highway shallow grouting repair process, comprising the following steps: Hole arrangement, drilling and cleaning, pre-embedded sealing rings, grouting, hole sealing and pressure stabilization, and road surface restoration. The grouting adopts a two-component grouting material for double-liquid grouting. The two-component grouting material includes component A and component B. Component A includes a composite polyol, a catalyst, a uniform foaming agent and a toughening agent. Component B includes isocyanate, characterized in that the toughening agent includes nano-silicon dioxide and phytic acid in a weight ratio of (2-3.5):10, and the component B also includes surface-modified glass microspheres in an amount of 30wt%-40wt% of the amount of isocyanate.

2. A highway shallow grouting repair process according to claim 1, characterized in that: The surface modified glass microspheres are prepared by the following method: The glass microspheres are subjected to flotation treatment, hydroxylation treatment, and amino modification treatment to obtain the glass microspheres to be modified. Subsequently, the glass microspheres to be modified and MDI in a weight ratio of 2: (0.5-0.6) are dispersed in an organic solvent, and the reaction is stirred at a temperature of 78-82°C for 2-2.2h. After that, the solid matter is taken out, washed with an organic solvent, filtered under reduced pressure, and vacuum dried until the system reaches a constant weight to obtain surface-modified glass microspheres.

3. A highway shallow grouting repair process according to claim 1, characterized in that: The weight ratio of nano-silica to phytic acid is 3:

10.

4. A highway shallow grouting repair process according to claim 1, characterized in that: The amount of the surface modified glass microspheres used is 35 wt % of the amount of isocyanate used.

5. A highway shallow grouting repair process according to claim 1, characterized in that: The nano silicon dioxide is nano silicon dioxide modified by a silane coupling agent.

6. A highway shallow grouting repair process according to claim 1, characterized in that: The complex polyol comprises a polyol A with a molecular weight of 500 and a polyol B with a molecular weight of 5000, and the weight ratio of the polyol A to the polyol B is 80:(15-25).

7. A highway shallow grouting repair process according to claim 6, characterized in that: The weight ratio of the polyol A to the polyol B is 80:

20.

8. The shallow grouting repair process for highway according to claim 1 is characterized by: The foam leveling agent in the A component is prepared by the following method: The low hydrogen silicone oil and allyl polyether are placed in a negative pressure environment for dehydration respectively, and then mixed under the protection of an inert gas so that the molar ratio of Si-H to C=C in the system is 1:(3-4), chloroplatinic acid is added, and the temperature is raised to 105-110°C for reaction for 2-2.5 hours to obtain a uniform foaming agent.

9. A highway shallow grouting repair process according to claim 1, characterized in that: The amount of chloroplatinic acid added is 0.01-0.015wt‰ of the total amount of the low hydrogen silicone oil and the allyl polyether.